A mutation map for human glycoside hydrolase genes. (10th February 2020) - Hansen, Lars; Husein, Diab M; Gericke, Birthe; Hansen, Torben; Pedersen, Oluf; Tambe, Mitali A; Freeze, Hudson H; Naim, Hassan Y; Henrissat, Bernard; Wandall, Hans H; Clausen, Henrik; Bennett, Eric P
Abstract: Glycoside hydrolases (GHs) are found in all domains of life, and at least 87 distinct genes encoding proteins related to GHs are found in the human genome. GHs serve diverse functions from digestion of dietary polysaccharides to breakdown of intracellular oligosaccharides, glycoproteins, proteoglycans and glycolipids. Congenital disorders of GHs (CDGHs) represent more than 30 rare diseases caused by mutations in one of the GH genes. We previously used whole-exome sequencing of a homogenous Danish population of almost 2000 individuals to probe the incidence of deleterious mutations in the human glycosyltransferases (GTs) and developed a mutation map of human GT genes (GlyMAP-I). While deleterious disease-causing mutations in the GT genes were very rare, and in many cases lethal, we predicted deleterious mutations in GH genes to be less rare and less severe given the higher incidence of CDGHs reported worldwide. To probe the incidence of GH mutations, we constructed a mutation map of human GH-related genes (GlyMAP-II) using the Danish WES data, and correlating this with reported disease-causing mutations confirmed the higher prevalence of disease-causing mutations in several GH genes compared to GT genes. We identified 76 novel nonsynonymous single-nucleotide variations (nsSNVs) in 32 GH genes that have not been associated with a CDGH phenotype, and we experimentally validated two novel potentially damaging nsSNVs in the congenital sucrase-isomaltase deficiency gene, SI. Our study provides a global view of human GH genes and disease-causing mutations and serves as a discovery tool for novel damaging nsSNVs in CDGHs.